Generation Y's positive and negative eWOM: use of social media and mobile technology. Issue 2 (13th February 2017) - Zhang, Tingting (Christina); Abound Omran, Behzad; Cobanoglu, Cihan
Abstract : Purpose: This paper aims to explore the factors that influence Generation Y's positive or negative electronic word-of-mouth (eWOM) behavior via social media and mobile technology in the foodservice sector. Three types of dining experiences were examined: positive and negative customer experiences and negative customer service followed by a satisfactory recovery package. Design/methodology/approach: A survey was adopted to test the factors posited to influence Generation Y consumers in these service contexts. Participants were recruited through Amazon Mechanical Turk, and multi-group structural equation modeling was performed to analyze the data. Findings: Active use of social media and peer influence had a sweeping influence on Generation Y's intentions to engage in eWOM about their service experiences. Technological sophistication with mobile technology influenced Generation Y to spread positive or negative service experiences, rather than satisfactory recovery experiences. Family influence had a mixed influence on Generation Y subgroups (21-24 years old vs 25-35 years old) to engage in eWOM about their satisfactory or poor service experiences. In satisfactory recovery experiences, family influence showed no significant influence on Generation Y's eWOM behaviors. Research limitations/implications: This study enriches online reviews and eWOM marketing theories, adds to service failure and recovery literature and enhances understanding of consumer behavior expressed by Generation Y through the empirical investigation of Generation Y consumers' behavioral motivations to engage in eWOM through social media and mobile technology. Practical implications: Engaging Generation Y consumers with social media campaigns and mobile technology development is not merely sufficient in eWOM marketing strategies. Instead, it is essential to create integrative peer communities to motivate Generation Y consumers to engage in eWOM marketing. Marketers need to pay attention to the mixed effects of family influences on the eWOM behaviors of subgroups of Generation Y in positive or negative service experiences. Originality/value: Given the scarcity of consumer behavior research into Generation Y as an emerging market segment, this paper makes an incremental contribution by developing and validating a model of factors that influence Generation Y consumers' eWOM intentions through social networking and mobile technologies in three major service contexts: positive, negative and recovery following a service failure.